Direct observation of ultrafast plasmonic hot electron transfer in the strong coupling regime - Shan, Hangyong (2019)
Achieving strong coupling between plasmonic oscillators can significantly modulate their intrinsic optical properties. Here, we report the direct observation of ultrafast plasmonic hot electron transfer from an Au grating array to an MoS2 monolayer in the strong coupling regime between localized surface plasmons (LSPs) and surface plasmon polaritons (SPPs). By means of femtosecond pump-probe spectroscopy, the measured hot electron transfer time is approximately 40 fs with a maximum external quantum yield of 1.65%. Our results suggest that strong coupling between LSPs and SPPs has synergetic effects on the generation of plasmonic hot carriers, where SPPs with a unique nonradiative feature can act as an ‘energy recycle bin’ to reuse the radiative energy of LSPs and contribute to hot carrier generation. Coherent energy exchange between plasmonic modes in the strong coupling regime can further enhance the vertical electric field and promote the transfer of hot electrons between the Au grating and the MoS2 monolayer. Our proposed plasmonic strong coupling configuration overcomes the challenge associated with utilizing hot carriers and is instructive in terms of improving the performance of plasmonic opto-electronic devices.